Impact of RFID on the Retail Value Chain: An Exploratory Study Using a Mixed Method Approach - Bhattacharya,Mithu (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2012)
While several large retailers have mandated RFID deployment across their value chains, the case for RFID adoption in retail still remains uncertain. This paper aims at providing a realistic perspective of the immense potential of RFID, taking adoption drivers, potential benefits, and implementation challenges into account. In this paper, a mixed methodological approach is used that caters to the exploratory nature of the work to quantitatively analyze RFID adoption drivers, benefits, and implementation challenges. First content analysis is applied to analyze academic and trade articles to come up with key issues and concepts. The results from the content analysis acted as input for a Delphi study which is the second methodology. The combined results from the two methods provide deep insights and enhance understanding of important implementation issues related to RFID adoption in the retail sector and also aid in drawing meaningful managerial conclusions.